X^{0}
= 1, X is not equal to 0. |

X^{1}
= X |

X^{(-a)}
= 1/X^{a} |

X^{a}X^{b}
= X^{a+b} |

(XY)^{a}
= X^{a}Y^{a} |

(X^{a})^{b}
= X^{ab} |

X^{a}/X^{b}
= X^{(a-b)}, X is not equal to 0. |

(X/Y)^{a}
= X^{a}/Y^{a}, X and Y are not equal to 0. |

(X/Y)^{a}
= X^{a}/Y^{a} |

X^{1/b}
= ,the
bth root of X |

X^{a/b}
= ,
the bth root of X raised to the a |

log_{b}(1)
= 0 |

log_{b}b
= 1 |

log_{b}
(x กม y) = log_{b}(x) + log_{b}(y) |

log_{b}(x/y)
= log_{b}(x) - log_{b}y |

log_{b}(x^{n})
= n log_{b}(x) |

Back to Formula